The manager as mentor - Marquardt, Michael J. (Manager as--, 2006)
One of the most valuable roles a manager can perform in today's rapidly changing environment is to mentor and inspire the people around them to learn. By nurturing talent, motivating individual development, and encouraging excellence, a manager's mentoring can enhance individual performance and the organization's prospects for success. Mentoring is not an easy skill to develop, and many managers, who may excel at leading or coaching, may be disasters as mentors when it comes to creating a bond and bringing out untapped qualities in others. The Manager as Mentor goes beyond traditional approach.